Prevalence of Paternal Prenatal Depression and Its Associated Factors in Saudi Arabia [Letter] - Shu P; Wang S; Jiang X (Dove Medical Press, 2024)
Pan Shu,1,* Song Wang,2,* Xiaolian Jiang2 1Department of Cardiology, West China Hospital/West China School of Nursing, Sichuan University, Chengdu, Sichuan, People’s Republic of China; 2West China School of Nursing/West China Hospital, Sichuan University, Chengdu, Sichuan, People’s Republic of China*These authors contributed equally to this workCorrespondence: Xiaolian Jiang, West China School of Nursing, West China Hospital, Sichuan University, No. 37, Guoxue Alley, Wuhou District, Chengdu, Sichuan, 610041, People’s Republic of China, Email jangxaolianhl@163.com